Distributed Source-Channel Coding Using Reduced-Complexity Syndrome-Based TTCM - Aljohani, Abdullah; Babar, Zunaira; Soon Xin Ng; Hanzo, Lajos (IEEE communications letters, 2016)
In the context of distributed joint source-channel coding, we conceive reduced-complexity turbo trellis coded modulation (TTCM)-aided syndrome-based block decoding for estimating the cross-over probability pe of the binary symmetric channel, which models the correlation between a pair of sources. Our joint decoder achieves an accurate correlation estimation for varying correlation coefficients at 3 dB lower SNR, than conventional TTCM decoder, despite its considerable complexity reduction.